Degenerative joint disease in weight-lifters. Fact or fiction?. Issue 2 (July 1980) - Fitzgerald, B.; McLatchie, G. R.
Abstract : A clinical and radiological study of upper and lower limb joints was carried out on 25 experienced weight-lifters to identify the extent of degenerative joint disease (Osteoarthrosis) produced by this sport. Although significant degenerative changes were found in five lifters (20%). This figure is not greater than that found in the general population within the age group studied. There were more degenerative changes found in Olympic style weight-lifters (30.7%) than in power lifters (8.3%). The significance of these figures is discussed. The upper limb joints were almost completely free of degenerative changes.